Characterization of an Aquaporin Gene ZpPIP2 from Zygophyllum potaninii - Bayarmaa Gun-Aajav; Munkhbileg Enkhbat; Oyuntsetseg Batlai (Mongolian Journal of Biological Sciences, 2016)
Zygophyllum potaninii Maxim. is a medicinal plant, distributed in arid regions of southern Mongolia. Full length of a cDNA clone, which was identifi ed as a stress induced gene by suppression subtractive hybridization was obtained by 5’RACEPCR, and named ZpPIP2 as deduced amino acid sequence shows high homology to plant aquaporin PIP2. ZpPIP2 is expressed in leaf and stem under normal conditions, and it is accumulated in the root in response to drought stress in Z. potaninii.